We need to simplify the expression <em>36x² - 49</em> , but let's recall the identity which is the main key to solve this question i.e
So , here we can write the above expression as
Now , using the above identity this can be written as :
So , here both <em>(6x-7)</em> and <em>(6x+7)</em> are factors of 36x²- 49 , but in the options their is only <em>6x - 7.</em>
<em>Hence , Option D) 6x - 7 is correct </em>
As here , <em>36x² = (6x)² = a²</em> , so <em><u>a = 6x</u></em> and as <em>49² = 7² = b²</em> , so <em><u>b = 7 </u></em>